Evaluation of direct-fed microbials on in vitro ruminal fermentation, gas production kinetic, and greenhouse gas emissions in different ruminants’ diet - Silva, Thiago H.; Amâncio, Bruna R.; Magnani, Elaine; Meurer, Gabriel W.; Reolon, Henrique G.; Timm, Thaynã G.; Cappellozza, Bruno I.; Branco, Renata H.; Paula, Eduardo M. (Frontiers in Animal Science, 2024)
Three in vitro experiments were conducted to evaluate the effects of increasing levels of Enterococcus faecium and Saccharomyces cerevisiae (DFM1) and increasing levels of Bacillus licheniformis and Bacillus subtilis (DFM2) on in vitro ruminal fermentation parameters in three different dietary scenarios. For Exp. 1, the basal diet consisted of 25:75 roughage:concentrate ratio (R:C) and was composed by 5 treatments: control (no additive), 2 levels of DFM1 (1X = 1.9 mg and 5X = 9.0 mg), and 2 levels of DFM2 (1X = 3.8 mg and 5X = 19 mg). The Exp. 2 consisted of a 41:59 R:C diet and was composed by 5 treatments: control (no additive) and 2 levels of DFM1 (1X = 3.8 mg and 5 X = 19 mg) and 2 levels of DFM2 (1X = 5.6 mg and 5X = 28 mg). The Exp. 3 consisted of a 100:0 R:C diet [Brachiaria (syn. Urochloa brizantha)] and was composed by the same treatments described in Exp. 1. The DFM1 contained 3.5 × 10 9 CFU per g of Enterococccus faecium and Saccharomyces cerevisiae, whereas the DFM2 contained Bacillus licheniformis and Bacillus subtilis at 3.2 × 10 9 CFU per g. In each Exp., an in vitro gas production (GP) system with 43-bottles (Ankom RF ) was used in four consecutive 48 or 72-h fermentation batches to evaluate total GP (TGP), kinetics and fermentation profiles, methane (CH4), and carbon dioxide (CO2). For Exp 1, DFM1 increased quadratically TGP at 24 and 48-h, which reflected in a greater in vitro organic matter digestibility (IVOMD). The concentrations of ammonia-N, CH4, and CO2 (mmol/g of IVOMD) reduced quadratically as DFM1 increased. For Exp. 2, DFM1 inclusion reduced butyrate concentration and acetate to propionate ratio. Regarding GHG emissions, DFM1 and DFM2 quadratically reduced CH4 and CO2 emission per IVOMD (mmol/g of IVOMD). For Exp. 3, DFM1 increased quadratically TGP at 48h with no impact on IVOMD. Otherwise, DFM2 increased linearly TGP at 24 and 48h which reflected in a greater IVOMD. The inclusion of DFM1 increased linearly iso-valerate and branched-chain volatile fatty acids (BCVFA) concentration and DFM2 addition increased BCVFA quadratically.